It's like being in a little psychological pressure cooker sometimes! A qualitative study of stress and coping in pre-qualification clinical psychology. Issue 3 (8th May 2017) - Galvin, John; Smith, Andrew Paul
Abstract : Purpose: The purpose of this paper is to investigate the stressors involved in pre-qualification clinical psychology as reported by a sample of the UK trainee clinical psychologists. The main coping strategies reported by the trainees are also explored. Design/methodology/approach: One-to-one interviews were conducted with 15 trainee clinical psychologists using qualitative research methods. Themes were established using the main principles of thematic analysis. Findings: Three themes were identified that described the pressures involved in applying to the course, the support networks available to trainees, and the commonalities in their personal history, experiences and self-reported personality characteristics. Originality/value: It is important to investigate the sources of stress and coping strategies in trainees to help them cope more effectively. The findings of the study are discussed within the context of clinical psychology training.